Strategi Marketing Public Relatios “Mobil Maung” di PT. Pindad (Persero) - Wira Naufal Ariq; Tresna Wiwitan (UNISBA Press, 2022)
Abstract. Entering the era of globalization where the competition is getting sharper, the marketing era has made significant progress with the existence of technology. Especially now that producers are advancing to attract the attention of the public or consumers as much as possible through digital information and digital marketing. In business, there is always competition, change, progress and uncertainty. Seeing the increasingly fierce competition, companies must have a Marketing Public Relations Strategy that is right on target. PT. Pindad (Persero) is a State-Owned Enterprise (BUMN) which is engaged in security and defense. PT. Pindad (Persero) which has also attracted the attention of the public lately is the manufacture of